SOCIAL MOVEMENTS AND POLICY CHANGE: UNDERSTANDING THE INTERPLAY BETWEEN ACTIVISM AND LEGISLATION - Zahoor Ahmad Ahanger; Javid Ahmad Kumar; Nadeem Mohi Ud Din; Shakeel Ahmad Ahanger (Journal of Accounting Research, Utility Finance and Digital Assets, 2025)
Social movements have long played a pivotal role in advocating for social, political, and economic change, often serving as a catalyst for policy reform. This paper examines the relationship between activism and legislation, focusing on the processes through which social movements influence policy change. By exploring key theoretical frameworks, such as Resource Mobilization Theory, Political Process Theory, and Framing Theory, the paper highlights how social movements mobilize resources, create political pressure, and shape public discourse to achieve legislative outcomes. Case studies, including the Civil Rights Movement, feminist movements, LGBTQ+ rights activism, and climate change advocacy, illustrate the practical implications of these theories. This study discusses the factors that impact the success of movements, including media influence, political environment, and leadership. Through a comprehensive analysis, this paper provides valuable insights into the complex interplay between social movements and legislative change, contributing to a deeper understanding of the role of activism in shaping public policy.